Change in paradise : Groote Eylandt, development, 1960-1974 - Taylor, Jim ([Darwin, N.T.] : Historical Society of the Northern Territory, 2013)
Annotation pending.
Part 1. Groote Eylandt -- Early days, Oenpelli -- Groote Eylandt 1960 -- Groote Eylandt, development -- Development; a consistent progression -- Industry arrives -- Part 2. Of various incidents in my life on Groote -- Epilogue.
"Jim Taylor came to Australia with his mother, coal mining engineer father and younger brother. They lived in Sydney for two years where Jim commenced a fitter and turner apprenticeship. The move to Lithgow changed this to a tool maker. He became increasingly interested in mission work and studied at Moore Theological College in Sydney. He was ordained as an Anglican Priest in 1958 moving to the Territory in 1960 with his wife and two young children to work for the Church Missionary Society. He served as the Superintendant of the CMS Mission at Angurugu, Groote Eylandt, for nearly 14 years before returning to Sydney. He then worked as an Anglican minister in various places but mainly in the Territory. He retired in Darwin before moving to Denmark in Western Australia in 2002".---back cover.
Keywords: Church Missionary Society of Australia -- History; Church of England -- Missions; Aboriginal Australians -- Missions -- Northern Territory -- History; Aboriginal Australians -- Missions -- Northern Territory -- Groote Eylandt; History - Biographies - Non-Indigenous - Autobiographies; Gender relations - Marriage; Religions - Christianity - Missions - Church Missionary Society; Community development - Infrastructure and municipal services - Housing; Mining industry - Manganese; Weapons - Spears - Fighting; Transport - Water - Canoes; Weapons - Clubs and fighting sticks - Fighting; Social events - Weddings; Religions - Christianity - Missionaries; Occupations - Domestic servants; Community development - Infrastructure and municipal services; Groote Eylandt (N.T.) -- Anecdotes; Groote Eylandt (N.T.) -- Church history; Gunbalanya / Oenpelli (West Arnhem Land NT SD53-01); Mud Cod Bay (Groote Eylandt NT Gulf Islands SD53-08); Angurugu (Groote Eylandt NT Gulf Islands SD53-07); Australian